Citrulline Generation Test: What Does It Measure?. Issue 6 (24th October 2018) - Mohammad, Mahmoud A.; Didelija, Inka C.; Stoll, Barbara; Marini, Juan C.
Abstract: Background: The citrulline generation test (CGT) has been proposed as a tool to determine gut function. However, the increase in plasma citrulline concentration that follows a bolus dose of alanyl‐glutamine may also result from a reduction in citrulline clearance due to competition with glutamine for transport. Materials and Methods: A swine model was developed, and stable isotope tracers were used to determine the mechanism behind the increase in plasma citrulline that follows a bolus dose of alanyl‐glutamine. Plasma concentrations and enrichments were determined, and a non–steady‐state model was used to calculate rates of appearance, disappearance, and conversion. Results: The pig model recapitulated the increase in plasma citrulline observed in humans after a dose of alanyl‐glutamine. The dipeptide was rapidly hydrolyzed to its constitutive amino acids. Both citrulline plasma concentration and citrulline rate of appearance increased by ≈45% after the bolus dose of alanyl‐glutamine. The conversion of citrulline to arginine and the rate of appearance of arginine also increased. Glutamine contributed up to 25% ± 2% of the rate of appearance of citrulline. No changes in the rate of disappearance of citrulline were observed. Conclusion: Our results indicate that a single bolus dose of alanyl‐glutamine increases plasma citrulline concentration by increasing citrulline production without any effect on citrulline disposal. Our findings strongly indicate that the CGT assesses the metabolic response of the gut and that CGT can become a useful tool to evaluate gut mass and function.